Prostate cancer detection in younger men: a comparative analysis of systematic and magnetic resonance imaging-targeted biopsy in the PROBASE trial - Monajjed, Rouvier Al-; Boschheidgen, Matthias; Lakes, Jale; Krilaviciute, Agne; Radtke, Jan Philipp; Schlemmer, Heinz-Peter; Bonekamp, David; Herkommer, Kathleen; Jahnen, Matthias; Gschwend, Jürgen E.; Düx, Daniel; Wacker, Frank; et al. (European urology, 2025)
The optimal approach for prostate cancer (PC) screening, including the ideal starting age and most effective diagnostic method, remains under investigation. We evaluated the diagnostic performance of magnetic resonance imaging (MRI)-targeted biopsy (TBx) and systematic biopsy (SBx) in detecting clinically significant PC (csPC) in men aged 45-50 yr in PROBASE, a prospective, randomized trial of a risk-adapted screening strategy. A total of 525 participants with elevated prostate-specific antigen (≥3 ng/ml) underwent MRI followed by biopsy. Of the 209 PC cases detected, 148 (71%) were csPC. SBx identified 94% of csPC cases, while TBx detected 74% (p ≤ 0.05). SBx also diagnosed significantly more low-grade PCs than TBx (p < 0.001). These findings suggest that relying solely on MRI-TBx may lead to underdiagnosis of csPC. Combining SBx with TBx remains the most effective strategy for early detection of PC in young men undergoing screening. Future research should explore optimization strategies to reduce unnecessary biopsies while maintaining high detection rates for csPC. This trial is registered on the ISRCTN registry as ISRCTN37591328 (https://www.isrctn.com/ISRCTN37591328). The study protocol can be accessed at https://doi.org/10.1016/j.eururo.2013.05.022.
Gesehen am 25.02.2026